A new device for endoscopic band ligation for colorectal diverticular bleeding - Daisuke Kikuchi; Junnosuke Hayasaka; Hironori Uruga; Takeshi Fujii; Yorinari Ochiai; Shu Hoteya (Endoscopy International Open, 2022)
Background and study aims Endoscopic band ligation (EBL) has been reported to be effective for colorectal diverticular bleeding. However, current EBL devices have some limitations, and we have developed a novel EBL device. Methods This novel EBL device has a tapered hood attached to the tip of the endoscope and an outer cylinder that loads two EBL bands. Twelve EBL procedures were performed in a live porcine model alternately using a conventional EBL device (Group C) and the novel EBL device (Group N). Results EBL was successful in all cases in both groups. There were no cases of perforation in the 10 days after EBL. After ligation, the mean major axis of the ridge was significantly larger in Group N than Group C (9.7 ± 1.4 mm vs 7.2 ± 1.4 mm, P = 0.011). Pathological examination revealed disruption of the muscularis propria at four of the six ligation sites in Group C and at five of the six ligation sites in Group N. Conclusions Using this novel EBL device, it was possible to perform multiple ligation procedures in succession with a good field of view. No perforation was observed, but disruption of the muscularis propria was observed at approximately three-quarters of the ligation sites pathologically.